Relics of the Reich : the buildings the Nazis left behind - Philpott, Colin (Pen & Sword Military, 2016)
Collective guilt? -- Establishing the faith -- Strength through joy -- Enforcement -- Showing off to the world -- Future fantasies -- War and implosion -- Holocaust -- Downfall -- Coming to terms with the past